UPAYA PEMBINAAN TERTIB ADMINISTRASI DESA OLEH DINAS PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA KABUPATEN SINTANG - Antonius Erwandi (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2020)
The orderly administration of the village becomes the authority of the Sintang District Village Empowerment and Village Administration Office which aims to achieve good and effective village government performance in its administration system. The research method used is a qualitative descriptive approach, data analysis techniques are qualitative, the tools used are Observation Guide, Interview Guidelines and documentation. The subjects of the study were 5 people, namely the Head of the Sintang District Village Community Empowerment and Village Empowerment Office, Sintang District Village Empowerment and Community Empowerment Office Secretary, Sintang District Village Empowerment and Community Empowerment Office Administration Staff, the Administrative Staff of the Sintang District Village Community Empowerment and Government Administration Office. Village Chief in Sintang Regency 2 people. Implementation of Administrative Guidance is carried out on an ongoing basis through technical guidance, work meetings and direct visits tovillages, Coordination in the Implementation of Administrative Coaching is carried out internally in the Office of Community Empowerment and Village Government by the Head of the Institutional Section because of the interrelated coaching from various aspects such as finance and also administrative order , Supervision of the implementation of Administrative Development together according to the authority of the Office of Community Empowerment and Village GovernmentKeywords: Efforts, Guidance, Orderly Administration.